Stress T1 Mapping in Hypertrophic Cardiomyopathy: Investigating Adenosine Administration Time for Adequate Vasodilation - Sang Il Choi (Journal of the Korean Society of Radiology)
Purpose This study aimed to evaluate the adequate adenosine administration time for stress T1 mapping in patients with hypertrophic cardiomyopathy (HCM). Materials and Methods Ten patients with HCM underwent cardiac MRI, including rest and adenosine stress T1 mapping, as well as late gadolinium enhancement. Myocardial T1 values for stress T1 reactivity (ΔT1) were evaluated. Stress T1 values measured at 1, 3, and 5 minutes after adenosine administration were compared with the native T1 value using a paired t-test. Results The stress T1 value at 5 minutes was the highest, followed by 3 minutes, 1 minute, and the native T1 value (1389 ± 16 vs. 1372 ± 19, 1354 ± 23, 1325 ± 23; all p < 0.001). The relationship between ΔT1 in each stress T1 map at 1, 3, and 5 minutes showed that ΔT1 at 3 and 5 minutes was significantly higher in all segments compared to that at 1 minute (4.83% ± 3.63%, 6.09% ± 3.97% vs. 2.96% ± 3.61%; p = 0.01, p = 0.006). However, ΔT1 at 5 minutes did not significantly differ from that at 3 minutes (4.83% ± 3.63%, 6.09% ± 3.97%; p = 0.237). Conclusion Adenosine administration for 3 minutes is adequate for stress T1 mapping in patients with hypertrophic cardiomyopathy.